2009
DOI: 10.1016/j.seizure.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Speech and school performance in children with benign partial epilepsy with centro-temporal spikes (BCECTS)

Abstract: Both deficits of speech-related abilities (in both expressive and receptive vocabulary) and behavioral disturbances can be detected in children with typical BCECTS, but are no longer apparent after remission of the seizure disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 47 publications
3
73
0
8
Order By: Relevance
“…Impairment of language development is one symptom of active epilepsy in children. Several case reports have described an association between nocturnal epileptiform EEG discharges and language impairment [1]. This is partly confirmed in some of the studies that investigated the effect of nocturnal epileptiform EEG discharges on neurocognitive function [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Impairment of language development is one symptom of active epilepsy in children. Several case reports have described an association between nocturnal epileptiform EEG discharges and language impairment [1]. This is partly confirmed in some of the studies that investigated the effect of nocturnal epileptiform EEG discharges on neurocognitive function [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 72%
“…However, several studies have demonstrated cognitive impairment in children with Rolandic epilepsy [1,6,[13][14][15]. In particular language impairment may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Normal neurocognitive function and outcome was classically an integral feature of these syndromes. However, detailed neuropsychological examination may reveal mild cognitive dysfunction in several domains, and-in the setting of additional neuropsychological testing in recent years-there is an increased prevalence of language, learning, and behavioral disorders (Croona et al, 1999;Fejerman, 2009;Germano et al, 2005;Gulgonen et al, 2000;Metz-Lutz and Filippini, 2006;Panayiotopoulos et al, 2008;Pinton et al, 2006;Sart et al, 2006;Vinayan et al, 2005;Völkl-Kernstock et al, 2009). Evolution of atypical BECTS into BOEC illustrates this spectrum (Caraballo et al, 2008).…”
Section: Bects and Boecmentioning
confidence: 99%
“…Because of the increasing awareness of significant comorbidities in RE, its classification as benign is under debate (Hughes, 2010;Nicolai et al, 2006;Vinayan et al, 2005;Völkl-Kernstock et al, 2009;Weglage et al, 1997). In the current study, we report widespread cortical abnormalities in language areas in children with RE who were selected based on EEG criteria and seizure semiology and not on language performance.…”
Section: Clinical Outlookmentioning
confidence: 99%
“…Although the seizure semiology of RE is relatively mild (Lerman and Kivity, 1975;Loiseau et al, 1992), recent evidence suggests serious comorbidities in selected cases and has put the assumed purely benign nature of RE under debate (Nicolai et al, 2006;Vinayan et al, 2005;Völkl-Kernstock et al, 2009;Weglage et al, 1997). An often reported comorbidity of RE is language impairment (Monjauze et al, 2005;Northcott et al, 2007;Overvliet et al, 2010;Papavasiliou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%